BIBLIOMETRIC ANALYSIS AND VISUAL MAPPING OF RESEARCH TRENDS IN SOUTH NIAS HOMBO BATU ETHNOPHYSICS WITHIN HIGH SCHOOL PHYSICS CURRICULUM VIA VOSVIEWER - Darmawan Harefa (FAGURU: Jurnal Ilmiah Mahasiswa Keguruan, 2026)
Physics instruction in secondary education often lacks cultural contextualization, causing students to view scientific concepts as abstract and detached from their everyday environment. This study presents a bibliometric analysis and visual network mapping of research trends in Hombo Batu (stone jumping) ethnophysics to evaluate its integration into the high school physics curriculum, specifically at SMA Negeri 1 Telukdalam. Utilizing VOSviewer, literature data from 2014 to 2024 were systematically analyzed to map co-occurrence networks, thematic density, and research trajectories. The bibliometric mapping revealed three primary clusters: classical mechanics concepts (parabolic kinematics, momentum, impulse), problem-based pedagogical frameworks, and local wisdom preservation. Despite extensive theoretical documentation in the existing literature, a critical empirical gap exists regarding classroom implementation in local schools. Applying these findings to SMA Negeri 1 Telukdalam demonstrates that Hombo Batu serves as a powerful context for teaching Class X mechanics under the Kurikulum Merdeka, effectively transforming abstract formulas into tangible physical phenomena. Connecting indigenous Nias traditions with modern science education enhances students' conceptual understanding while reinforcing their cultural identity. Ultimately, this research provides an evidence-based roadmap for educators at SMA Negeri 1 Telukdalam to operationalize ethnophysics in secondary science education.